patch

The patch design for bronanserine, incorporating a rubber-based adhesive base, organic acid, and tackifier, addresses the issues of storage stability and bleed-out, ensuring consistent and controlled drug delivery.

JP2025064370APending Publication Date: 2025-04-17TOYO INK MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023174071
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-06
Publication Date
2025-04-17

AI Technical Summary

Technical Problem

The use of rubber-based adhesive bases in bronanserine patches leads to reduced storage stability due to bronanserine precipitation, and the addition of organic acids to improve stability can result in bleed-out, affecting adhesive strength and leading to potential overdose.

Method used

A patch design that incorporates a rubber-based adhesive base, bronanserine, an organic acid, and a tackifier with an acid value of less than 2 mgKOH/g, where the molar ratio of the organic acid to bronanserine is 0.30 or more, and the mass ratio is less than 0.45, to reduce bleed-out and enhance storage stability.

Benefits of technology

The proposed patch design effectively reduces the bleed-out of organic acids, maintaining the adhesive strength and storage stability of bronanserine, thereby preventing premature precipitation and ensuring consistent drug delivery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025064370000001
    Figure 2025064370000001
  • Figure 2025064370000002
    Figure 2025064370000002
Patent Text Reader

Abstract

To provide a patch in which an organic acid is included in an adhesive layer, but bleed-out of the organic acid is suppressed, while ensuring excellent storage stability of blonanserin.SOLUTION: A patch of the present invention comprises a support and an adhesive layer laminated and integrated on one surface of the support, where the adhesive layer contains blonanserin, a rubber-based adhesive base, an organic acid, and a tackifier (B1) having an acid value of less than 2 mgKOH / g. In the adhesive layer, the molar ratio of the organic acid to the blonanserin is 0.30 or more, and the mass ratio of the organic acid to the blonanserin is less than 0.45.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a patch containing blonanserin as a drug. [Background technology]

[0002] Blonanserin is known as a therapeutic drug for schizophrenia.

[0003] Blonanserin is sold as an oral preparation (trade name "Lonasen Tablets" and "Lonasen Powder" manufactured by Sumitomo Dainippon Pharma Co., Ltd.). However, oral preparations can cause problems such as degradation due to the first-pass effect in the liver, occurrence of gastrointestinal disorders, and occurrence of side effects due to rapid fluctuations in blood concentration.

[0004] Therefore, a patch containing blonanserin has been proposed. By attaching the patch to the skin, blonanserin can be administered transdermally into the body.

[0005] The patch has a support and an adhesive layer laminated and integrated on one surface of the support. The adhesive layer contains blonanserin and an adhesive base. The adhesive base used may be an acrylic adhesive base or a rubber adhesive base (e.g., Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2007 / 142295 [Patent Document 2] International Publication No. 2021 / 230064 Summary of the Invention [Problem to be solved by the invention]

[0007] In patches containing blonanserin, rubber-based adhesive bases have good adhesion to the skin, are highly safe, and are superior to acrylic adhesive bases in that they are less susceptible to cold flow, which is a phenomenon in which the adhesive layer flows out from the sides of a patch over time during storage or application of the patch.

[0008] Therefore, it is desirable to use a rubber-based adhesive base as an adhesive base in a patch containing Blonanserin. However, Blonanserin has a lower solubility in a rubber-based adhesive base than an acrylic adhesive base. Therefore, Blonanserin precipitates as crystals in the adhesive layer during storage of the patch, which causes a problem of reduced storage stability. If Blonanserin precipitates, the transdermal absorbability of Blonanserin changes over time, and the expected medicinal effect may not be obtained.

[0009] Therefore, by using an organic acid such as lactic acid in addition to a rubber-based adhesive base in the adhesive layer, the storage stability of blonanserin can be improved.

[0010] However, according to the study by the present inventors, it was found that when an organic acid is added to the adhesive layer to improve the storage stability of Blonanserin, the organic acid may bleed out over time to the surface of the adhesive layer. Bleeding out of the organic acid causes the following problems. When the organic acid bleeds out to the surface of the adhesive layer on the skin side, the adhesive strength of the adhesive layer to the skin may decrease. In addition, since the organic acid has a high affinity with Blonanserin, Blonanserin also tends to migrate to the surface of the adhesive layer with the bleed-out of the organic acid, and as a result, Blonanserin may be over-administered to the body in a shorter time than the initial administration schedule. Furthermore, when the organic acid bleeds out to the support-side surface of the adhesive layer, at least a part of the adhesive layer may peel off from the support when the patch is peeled off from the skin, and the peeled part of the adhesive layer may remain on the skin. In such a case, Blonanserin continues to be administered to the body despite the peeling off of the patch, which causes over-administration of Blonanserin. Therefore, even if an organic acid is used for the storage stability of Blonanserin, it is desired to reduce the occurrence of bleed-out.

[0011] Therefore, an object of the present invention is to provide a patch in which, despite the adhesive layer containing an organic acid, bleed-out of the organic acid is reduced and the storage stability of blonanserin is also excellent. [Means for solving the problem]

[0012] The patch of the present invention comprises a support and an adhesive layer laminated and integrated on one surface of the support, The adhesive layer contains blonanserin, a rubber-based adhesive base, an organic acid, and a tackifier (B1) having an acid value of less than 2 mgKOH / g, The adhesive layer is characterized in that a molar ratio of the organic acid to the blonanserin is 0.30 or more, and a mass ratio of the organic acid to the blonanserin is less than 0.45.

[0013] In one embodiment of the present invention, the rubber-based adhesive base includes at least one of a styrene-based polymer and polyisobutylene. In one embodiment of the present invention, the rubber-based adhesive base comprises a styrene-isoprene-styrene block copolymer. In one embodiment of the invention, the organic acid comprises levulinic acid. In one embodiment of the present invention, the mass ratio of the tackifier (B1) to the organic acid in the adhesive layer is 12 or more and 50 or less. Effect of the Invention

[0014] According to the present invention, even though the adhesive layer contains an organic acid, the bleed-out of the organic acid is reduced, and a patch having excellent storage stability of blonanserin can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The patch of the present invention comprises a support and an adhesive layer laminated and integrated on one surface of the support, the adhesive layer containing blonanserin, a rubber-based adhesive base, an organic acid, and a tackifier (B1) having an acid value of less than 2 mgKOH / g, The adhesive layer is characterized in that a molar ratio of the organic acid to the blonanserin is 0.30 or more, and a mass ratio of the organic acid to the blonanserin is less than 0.45.

[0016] [Adhesive layer] The patch comprises an adhesive layer laminated integrally on one surface of the backing, the adhesive layer comprising blonanserin, a rubber-based adhesive base, an organic acid, and a tackifier (B1).

[0017] (Blonanserin) The adhesive layer contains the drug blonanserin, which has a strong blocking effect on dopamine D2 receptors and serotonin 2 (5-HT2A) receptors and is used as a treatment for schizophrenia.

[0018] Blonanserin includes free base type and acid addition salt type. The adhesive layer may contain at least one of free base type blonanserin and acid addition salt type blonanserin. Among them, free base type (free form) blonanserin (2-(4-ethyl-1-piperazinyl)-4-(4-fluorophenyl)-5,6,7,8,9,10-hexahydrocycloocta[b]pyridine) is preferred. Free base type blonanserin can provide a patch with better transdermal absorption of blonanserin.

[0019] Blonanserin in the form of an acid addition salt is a physiologically acceptable acid addition salt of Blonanserin in the form of a free base. Physiologically acceptable acid addition salts include, but are not limited to, inorganic acid salts such as hydrochloride, hydrobromide, nitrate, sulfate, and phosphate; organic acid salts such as formate, acetate, trifluoroacetate, ascorbate, benzoate, cinnamate, citrate, fumarate, glutamate, tartrate, oxalate, glutarate, camphorate, adipate, sorbate, lactate, maleate, linoleate, linolenate, malate, malonate, mandelate, methanesulfonate (mesylate), phthalate, salicylate, stearate, isostearate, succinate, propionate, butyrate, pamoate, p-toluenesulfonate (tosylate), and benzenesulfonate (besylate). The acid addition salt type blonanserin may be used alone or in combination of two or more kinds.

[0020] The content of Blonanserin in the adhesive layer is preferably 0.5% by mass or more, more preferably 0.75% by mass or more, more preferably 1% by mass or more, more preferably 3% by mass or more, and more preferably 5% by mass or more. The content of Blonanserin in the adhesive layer is preferably 50% by mass or less, more preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 20% by mass or less, more preferably 10% by mass or less, and more preferably 8% by mass or less. By making the content rate of Blonanserin 0.5% by mass or more, the transdermal absorbability of Blonanserin can be sufficiently increased to a level required for treatment. By making the content of Blonanserin 50% by mass or less, the storage stability of Blonanserin can be improved.

[0021] The content of Blonanserin in the adhesive layer is the content converted into Blonanserin in free base form. That is, when Blonanserin contains an acid addition salt type Blonanserin, the mass of the acid addition salt type Blonanserin is the mass converted into Blonanserin in free base form. The mass of the acid addition salt type Blonanserin converted into Blonanserin in free base form is the mass of Blonanserin in free base form equimolar to the acid addition salt type Blonanserin. Specifically, the content of Blonanserin in the adhesive layer can be calculated based on the following formula. In the following formula, the mass of the acid addition salt type Blonanserin in the denominator "mass of adhesive layer" is not converted into Blonanserin in free base form. Blonanserin content in adhesive layer (% by mass)= 100 × (mass of free base blonanserin + mass of acid addition salt blonanserin converted to free base blonanserin) / (mass of adhesive layer)

[0022] (Rubber adhesive base) The adhesive layer includes a rubber-based adhesive base. The rubber-based adhesive base can impart an appropriate cohesive force to the adhesive layer and exhibit good adhesion to the skin. Examples of the rubber-based adhesive base include synthetic rubber and natural rubber. Specific examples of the rubber-based adhesive base include synthetic rubber such as styrene polymer, polyisobutylene, polybutadiene, and polyisoprene, and natural rubber. Among them, styrene polymer and polyisobutylene are preferred. The rubber-based adhesive base may be used alone or in combination of two or more kinds.

[0023] The rubber-based adhesive base preferably does not have an acidic functional group in the molecule. Examples of the acidic functional group include a carboxyl group (-COOH), a sulfonic acid group, and a phosphoric acid group (H2PO4-). Examples of the phosphoric acid group include the phosphoric acid group represented by the following chemical formula (1) described later in the description of the tackifier (B1).

[0024] As the styrene-based polymer, a styrene-based block copolymer is preferred. Specifically, styrene-butadiene block copolymer (SB), styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene block copolymer (SI), styrene-isoprene-styrene block copolymer (SIS), styrene-(ethylene / butylene) block copolymer (SEB), styrene-(ethylene / butylene)-styrene block copolymer (SEBS), styrene-(ethylene / propylene) block copolymer (SEP), styrene-(ethylene / propylene)-styrene block copolymer (SEPS), styrene-ethylene-(ethylene / propylene)-styrene block copolymer (SEEPS), styrene-isobutylene block copolymer, and styrene-isobutylene-styrene block copolymer are listed. Among them, styrene-isoprene-styrene block copolymer (SIS) is preferred. The styrene-based polymer may be used alone or in combination of two or more.

[0025] The content of the styrene unit in the styrene polymer is preferably 5% by mass or more, more preferably 10% by mass or more, and more preferably 14% by mass or more. The content of the styrene unit in the styrene polymer is preferably 60% by mass or less, more preferably 50% by mass or less, and more preferably 40% by mass or less. By making the content of the styrene unit 5% by mass or more, it becomes easier to impart a suitable adhesive strength to the adhesive layer. By making the content of the styrene unit 60% by mass or less, it becomes easier to impart a suitable flexibility to the adhesive layer, which makes it easier for the patch to follow the movement of the skin.

[0026] The viscosity of a 25% by mass toluene solution of the styrene-isoprene-styrene block copolymer at 25°C is preferably 500 mPa·s or more, more preferably 900 mPa·s or more. The viscosity of a 25% by mass toluene solution of the styrene-isoprene-styrene block copolymer at 25°C is preferably 2000 mPa·s or less, more preferably 1800 mPa·s or less, and more preferably 1500 mPa·s or less. When the viscosity is 500 mPa·s or more, it is easy to impart a suitable cohesive force to the adhesive layer. When the viscosity is 2000 mPa·s or less, it is possible to form an adhesive layer having a uniform thickness, thereby improving the transdermal absorbability of blonanserin.

[0027] The 25% by mass toluene solution of styrene-isoprene-styrene block copolymer means a solution containing 25% by mass of styrene-isoprene-styrene block copolymer in toluene as a solvent. The viscosity of the 25% by mass toluene solution of styrene-isoprene-styrene block copolymer can be measured in accordance with the viscosity measurement method for styrene-isoprene-styrene block copolymer described on page 395 of "Pharmaceutical Additives Standards 2013" (published by Yakuji Nipposha).

[0028] As the styrene-isoprene-styrene block copolymer, commercially available products can be used. Examples of commercially available products include those manufactured by Zeon Corporation under the trade names "Quintac (registered trademark) 3421", "Quintac (registered trademark) 3433N", "Quintac (registered trademark) 3520", "Quintac (registered trademark) 3450", and "Quintac (registered trademark) 3270"; those manufactured by KRATON POLYMERS under the trade names "KRATON (registered trademark) D1111", "KRATON (registered trademark) D1163", "KRATON (registered trademark) D1113", and "KRATON (registered trademark) D1119"; and those manufactured by JSR Corporation under the trade names "JSR (registered trademark) SIS5229", "JSR (registered trademark) SIS5002", "JSR (registered trademark) SIS5403", and "JSR (registered trademark) SIS5505".

[0029] The content of the styrene polymer in the rubber-based adhesive base is preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 85% by mass or more, and even more preferably 95% by mass or more. By making the content of the styrene polymer 50% by mass or more, the adhesive layer can have a more appropriate cohesive force and can have a higher adhesiveness to the skin.

[0030] The content of the rubber-based adhesive base in the adhesive layer is preferably 10% by mass or more, more preferably 15% by mass or more, more preferably 20% by mass or more, more preferably 25% by mass or more, and more preferably 30% by mass or more. The content of the rubber-based adhesive base in the adhesive layer is preferably 70% by mass or less, more preferably 65% ​​by mass or less, and more preferably 55% by mass or less. By making the content of the rubber-based adhesive base 10% by mass or more, it becomes easier to more reliably maintain the shape of the adhesive layer. By making the content of the rubber-based adhesive base 70% by mass or less, it becomes easier to exhibit more appropriate adhesion to the skin.

[0031] (organic acid) The adhesive layer contains an organic acid. The organic acid can improve the storage stability of blonanserin. The organic acid preferably excludes the tackifier (B1). The organic acid preferably excludes the tackifier (A).

[0032] Examples of organic acids include monocarboxylic acids such as lactic acid, propionic acid, capric acid, sorbic acid, salicylic acid, gallic acid, acetic acid, butyric acid, valeric acid, levulinic acid, lauric acid, myristic acid, stearic acid, isostearic acid, and oleic acid; dicarboxylic acids such as adipic acid, maleic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, fumaric acid, phthalic acid, isophthalic acid, terephthalic acid, malic acid, and sebacic acid; and tricarboxylic acids such as citric acid. Among these, monocarboxylic acids are preferred, and lactic acid, levulinic acid, and oleic acid are more preferred, and levulinic acid is more preferred. The organic acids may be used alone or in combination of two or more.

[0033] The melting point of the organic acid is preferably -50 to 100°C, more preferably -30 to 40°C. An organic acid having a melting point within the above range can further improve the storage stability of blonanserin, while an organic acid having a melting point within the above range is likely to bleed out onto the surface of the adhesive layer. However, in the present invention, the bleed-out of the organic acid can be reduced by using an organic acid at a predetermined molar ratio and mass ratio to blonanserin in the adhesive layer containing the tackifier (B1). Therefore, it is preferable to use an organic acid having a melting point within the above range, as this is particularly likely to exhibit the effects of the present invention.

[0034] The melting point of the organic acid can be measured by thermal analysis using a differential scanning calorimeter (DSC).

[0035] In the adhesive layer, the molar ratio of the organic acid to Blonanserin (moles of organic acid / moles of Blonanserin) is 0.30 or more, more preferably 0.45 or more. In addition, in the adhesive layer, the molar ratio of the organic acid to Blonanserin (moles of organic acid / moles of Blonanserin) is preferably 1.45 or less, more preferably 1.35 or less, more preferably 1.15 or less, and more preferably 0.70 or less. By making the molar ratio of the organic acid 0.30 or more, the storage stability of Blonanserin can be further improved. In addition, by making the molar ratio of the organic acid 1.45 or less, the bleeding out of the organic acid on the adhesive layer surface over time can be reduced.

[0036] In the adhesive layer, the mass ratio of the organic acid to Blonanserin (mass of organic acid / mass of Blonanserin) is preferably 0.01 or more, more preferably 0.05 or more, and more preferably 0.10 or more. In addition, in the adhesive layer, the mass ratio of the organic acid to Blonanserin (mass of organic acid / mass of Blonanserin) is less than 0.45, preferably 0.35 or less, more preferably less than 0.25, and more preferably 0.20 or less. By making the mass ratio of the organic acid 0.01 or more, the storage stability of Blonanserin can be further improved. In addition, by making the mass ratio of the organic acid less than 0.45, the bleeding out of the organic acid on the adhesive layer surface over time can be reduced.

[0037] In addition, in calculating the mass ratio or molar ratio of the components in the adhesive layer of the patch of the present invention, the mass of the acid addition salt form of Blonanserin converted into the mass of free base form of Blonanserin is used as the mass of the acid addition salt form of Blonanserin. The mass of the acid addition salt form of Blonanserin converted into the mass of free base form of Blonanserin is the mass of the free base form of Blonanserin in an amount equimolar to the acid addition salt form of Blonanserin. Examples of the mass ratio or molar ratio of the components in the adhesive layer include the molar ratio of the organic acid to Blonanserin, and the mass ratio of the organic acid to Blonanserin.

[0038] The content of the organic acid in the adhesive layer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, more preferably 0.7% by mass or more, and more preferably 1% by mass or more. The content of the organic acid in the adhesive layer is preferably 10% by mass or less, more preferably 8% by mass or less, more preferably 5% by mass or less, and more preferably 1.5% by mass or less. By making the content of the organic acid 0.1% by mass or more, the storage stability of blonanserin can be further improved. By making the content of the organic acid 10% by mass or less, the bleed-out of the organic acid can be easily reduced.

[0039] (Tackifier (B1)) The adhesive layer comprises a tackifier (B1) having an acid value of less than 2 mg KOH / g.

[0040] The acid value of the tackifier (B1) is less than 2 mgKOH / g, and more preferably 1 mgKOH / g or less. The acid value of the tackifier (B1) is preferably 0 mgKOH / g or more. The tackifier (B1) has an acid value of less than 2 mgKOH / g, and therefore has excellent compatibility with the rubber-based adhesive base. Therefore, by using such a tackifier (B1), the elastic modulus of the rubber-based adhesive base can be appropriately reduced, and the adhesive strength of the adhesive layer can be appropriately improved.

[0041] The acid value of the tackifier can be measured by a method based on the potentiometric titration method of JIS K0070 (1992).

[0042] The tackifier (B1) preferably does not have an acidic functional group in the molecule. Examples of the acidic functional group include a carboxyl group (-COOH), a sulfonic acid group, and a phosphoric acid group (H2PO4-) represented by the following chemical formula (1).

[0043] [ka]

[0044] Examples of the tackifier (B1) include coumarone-indene resins, terpene resins, and petroleum resins. Among these, terpene resins and petroleum resins are preferred. The tackifier (B1) may be used alone or in combination of two or more kinds.

[0045] Examples of the terpene resin include terpene resin (polyterpene), aromatic modified terpene resin, and hydrogenated products thereof. Among them, terpene resin is preferable. Examples of the terpene resin include α-pinene polymer, β-pinene polymer, dipentene polymer, and the like. The terpene resin has excellent compatibility with rubber-based adhesive bases. It is preferable that the terpene resin does not have an acidic functional group in the molecule. The terpene resin may be used alone or in combination of two or more kinds.

[0046] Examples of the petroleum resin include aliphatic petroleum resin, alicyclic petroleum resin, aromatic petroleum resin, and hydrogenated products thereof. Among them, alicyclic petroleum resin and hydrogenated products thereof are preferred, and hydrogenated products of alicyclic petroleum resin are more preferred. These have an alicyclic structure in the molecule, and therefore have excellent compatibility with rubber-based adhesive base materials. It is preferable that the petroleum resin does not have an acidic functional group in the molecule. The petroleum resin may be used alone or in combination of two or more kinds.

[0047] The content ratio of the tackifier (B1) in the adhesive layer is preferably 10 parts by mass or more, more preferably 35 parts by mass or more, more preferably 50 parts by mass or more, and more preferably 80 parts by mass or more, relative to 100 parts by mass of the rubber-based resin. The content ratio of the tackifier (B1) in the adhesive layer is preferably 400 parts by mass or less, more preferably 350 parts by mass or less, more preferably 300 parts by mass or less, more preferably 200 parts by mass or less, more preferably 180 parts by mass or less, more preferably 130 parts by mass or less, and more preferably 120 parts by mass or less, relative to 100 parts by mass of the rubber-based resin. The tackifier (B1) is used to improve the adhesive strength of the adhesive layer. On the other hand, as described above, the tackifier (B1) has a low acid value, so that it has low compatibility with organic acids, and the addition of the tackifier (B1) may promote the bleeding out of organic acids to the surface of the adhesive layer. However, by setting the content ratio of the tackifier (B1) within the above range, excellent compatibility between the rubber resin and the tackifier (B1) can be ensured. This allows the rubber resin and the tackifier (B1) to be highly mixed in the adhesive layer, and allows the organic acid to maintain high compatibility with the entire adhesive layer. As a result, the organic acid is easily retained in the adhesive layer, and the bleeding out of the organic acid can be further reduced.

[0048] In the adhesive layer, the mass ratio of the tackifier (B1) to the organic acid (mass of tackifier (B1) / mass of organic acid) is preferably 9 or more, more preferably 12 or more, more preferably 15 or more, more preferably 20 or more, more preferably 25 or more, and more preferably 35 or more. In the adhesive layer, the mass ratio of the tackifier (B1) to the organic acid (mass of tackifier (B1) / mass of organic acid) is preferably 50 or less, more preferably 45 or less, and more preferably 40 or less. By setting the mass ratio (mass of tackifier (B1) / mass of organic acid) within the above range, it is possible to easily maintain the cohesive force of the adhesive layer and the storage stability of blonanserin.

[0049] The content of the tackifier (B1) in the adhesive layer is preferably 10% by mass or more, more preferably 15% by mass or more, more preferably 25% by mass or more, and more preferably 35% by mass or more. The content of the tackifier (B1) in the adhesive layer is preferably 70% by mass or less, more preferably 65% ​​by mass or less, more preferably 60% by mass or less, more preferably 50% by mass or less, more preferably 45% by mass or less, and more preferably 40% by mass or less. By making the content of the tackifier (B1) 10% by mass or more, it is possible to easily impart an appropriate adhesive strength to the adhesive layer. By making the content of the tackifier (B1) 70% by mass or less, it is possible to further reduce the bleeding out of the organic acid.

[0050] (Tackifier (A)) The adhesive layer may contain a tackifier (A) having an acid value of 2 mgKOH / g or more.

[0051] The acid value of the tackifier (A) is preferably 2 mgKOH / g or more. The acid value of the tackifier (A) is preferably 160 mgKOH / g or less, more preferably 130 mgKOH / g or less, and more preferably 20 mgKOH / g or less. By setting the acid value of the tackifier (A) within the above range, the solubility of Blonanserin in the adhesive layer is improved, and further improvement in the storage stability of Blonanserin can be expected.

[0052] The tackifier (A) preferably has an acidic functional group in the molecule. Examples of the acidic functional group include a carboxy group (-COOH), a sulfonic acid group, and a phosphoric acid group (H2PO4-) represented by the above chemical formula (1). Among them, the acidic functional group is preferably a carboxy group. The acidic functional groups may be used alone or in combination of two or more kinds.

[0053] The tackifier (A) may be a rosin-based resin. The tackifier (A) may be used alone or in combination of two or more kinds.

[0054] Examples of rosin-based resins include unmodified rosin, hydrogenated rosin, disproportionated rosin, polymerized rosin, α,β-unsaturated carboxylic acid modified rosin, and rosin ester. Among them, hydrogenated rosin, polymerized rosin, and rosin ester are preferred, and rosin ester is more preferred. The rosin-based resins may be used alone or in combination of two or more kinds.

[0055] The content ratio of the tackifier (A) in the adhesive layer is preferably less than 10 parts by mass, more preferably 5 parts by mass or less, more preferably 1 part by mass or less, more preferably 0.1 parts by mass or less, and more preferably 0.05 parts by mass or less, relative to 100 parts by mass of the rubber-based adhesive base. When the adhesive layer contains the tackifier (A), the content ratio of the tackifier (A) in the adhesive layer exceeds 0 parts by mass relative to 100 parts by mass of the rubber-based adhesive base. The lower the content ratio of the tackifier (A) in the adhesive layer, the easier it is to maintain the solubility of blonanserin in the adhesive layer within an appropriate range and to transfer blonanserin to the surface of the adhesive layer, thereby further improving the transdermal absorbability of blonanserin.

[0056] (Plasticizer) The adhesive layer preferably further contains a plasticizer, which can further improve the adhesiveness of the adhesive layer and further reduce irritation to the skin.

[0057] Examples of the plasticizer include fatty acid esters such as methyl laurate, hexyl laurate, isopropyl myristate, myristyl myristate, octyldodecyl myristate, isopropyl palmitate, and cetyl palmitate; fatty alcohols such as monohydric fatty alcohols such as myristyl alcohol, cetanol, octyldodecanol, isostearyl alcohol, and stearyl alcohol, and dihydric fatty alcohols such as octanediol; petroleum oils such as liquid paraffin, paraffin-based process oil, naphthenic process oil, and aromatic process oil; fatty acid amides such as lauric acid diethanolamide; and naturally derived oils and fats such as olive oil. The plasticizers may be used alone or in combination of two or more.

[0058] As the plasticizer, fatty acid ester, aliphatic alcohol, and petroleum oil are preferable, isopropyl myristate, isopropyl palmitate, octyldodecanol, isostearyl alcohol, stearyl alcohol, liquid paraffin, paraffin-based process oil, and naphthene-based process oil are more preferable, isopropyl myristate, octyldodecanol, and liquid paraffin are more preferable, and octyldodecanol is more preferable. These plasticizers can stably hold blonanserin in the adhesive layer and maintain the adhesive strength of the adhesive layer.

[0059] The content of the plasticizer in the adhesive layer is preferably 3% by mass or more, more preferably 5% by mass or more, more preferably 8% by mass or more, more preferably 10% by mass or more, and more preferably 15% by mass or more. The content of the plasticizer in the adhesive layer is preferably 50% by mass or less, more preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 25% by mass or less, more preferably 20% by mass or less, and more preferably 18% by mass or less. By setting the content of the plasticizer within the above range, the adhesiveness of the adhesive layer can be further improved.

[0060] The adhesive layer may also contain other additives, such as fillers and stabilizers.

[0061] (Filler) The filler is used to adjust the shape retention of the adhesive layer. Examples of the filler include inorganic fillers such as light anhydrous silicic acid, titanium oxide, and zinc oxide; organic metal salts such as calcium carbonate and magnesium stearate; cellulose derivatives such as lactose, crystalline cellulose, ethyl cellulose, and low-substituted hydroxypropyl cellulose; and crosslinked polyvinylpyrrolidone. The filler may be used alone or in combination of two or more. When the adhesive layer contains a filler, the content of the filler in the adhesive layer is preferably 5 parts by mass or less, more preferably 0.1 to 2 parts by mass, based on 100 parts by mass of the rubber-based adhesive base.

[0062] The thickness of the adhesive layer is preferably 10 μm or more, more preferably 20 μm or more, and particularly preferably 30 μm or more. The thickness of the adhesive layer is preferably 400 μm or less, more preferably 200 μm or less, and particularly preferably 150 μm or less. When the thickness of the adhesive layer is 10 μm or more, the adhesive layer can contain a necessary amount of drug to obtain a desired medicinal effect. When the thickness of the adhesive layer is 400 μm or less, strong drying conditions are not required during production to reduce the remaining solvent in the adhesive layer, so that the volatilization or decomposition of the drug in the adhesive layer can be suppressed.

[0063] [Support] In the patch of the present invention, an adhesive layer is laminated and integrated on one side of the support. The support is required to have strength to prevent loss of the drug in the adhesive layer and to impart self-retention to the patch. Examples of such supports include resin films, nonwoven fabrics, woven fabrics, knitted fabrics, and aluminum sheets.

[0064] Examples of resins constituting the resin film include ethyl cellulose, cellulose acetate, rayon, polyethylene terephthalate, plasticized vinyl acetate-vinyl chloride copolymer, nylon, ethylene-vinyl acetate copolymer, plasticized polyvinyl chloride, polyurethane, polyethylene, polypropylene, polyvinylidene chloride, etc. Among these, polyethylene terephthalate is preferred because it can prevent loss of the drug from the adhesive layer.

[0065] Examples of materials constituting the nonwoven fabric include polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ethylene-methyl (meth)acrylate copolymer, nylon, polyester, vinylon, SIS copolymer, SEBS copolymer, rayon, cotton, etc., with polyester being preferred. These materials may be used alone or in combination of two or more.

[0066] The support may be a single layer or a laminated sheet in which multiple layers are laminated together, such as a laminated sheet in which a polyethylene terephthalate film is laminated together with a nonwoven fabric or a flexible resin film.

[0067] The thickness of the support is not particularly limited, but is preferably 2 μm or more, and is preferably 200 μm or less, and more preferably 100 μm or less.

[0068] [Release liner] In the patch of the present invention, a release liner may be integrally laminated in a releasable manner on one side of the adhesive layer. The release liner is used to prevent loss of the drug in the adhesive layer and to protect the adhesive layer.

[0069] Examples of the release liner include paper, resin film, and metal foil. Examples of the resin constituting the resin film include polyethylene terephthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene chloride, etc. Examples of the metal foil include aluminum foil, etc. It is preferable that the surface of the release liner facing the adhesive layer is subjected to a release treatment.

[0070] [Method of manufacturing patch] Examples of methods for producing the patch of the present invention include: (1) a method in which a coating liquid containing blonanserin, a rubber-based adhesive base, an organic acid, a tackifier (B1), and a solvent, and optionally other additives, is applied to one side of a backing, followed by drying to laminate an adhesive layer onto one side of the backing, and, if necessary, a release liner is laminated onto the adhesive layer such that the release-treated surface of the release liner faces the adhesive layer; and (2) a method in which the coating liquid is applied to the release-treated surface of a release liner, followed by drying to form an adhesive layer on the release liner, and then the backing is laminated onto the adhesive layer.

[0071] The coating liquid is obtained by uniformly stirring Blonanserin, a rubber-based adhesive base, an organic acid, a tackifier (B1), a solvent, and other additives as necessary. Examples of the solvent include aromatic hydrocarbons such as toluene, alicyclic hydrocarbons such as cyclohexane and methylcyclohexane, aliphatic hydrocarbons such as hexane and heptane, ethers such as tetrahydrofuran, diethyl ether, and t-butyl methyl ether, ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, alcohols such as ethanol, propanol, and butanol, and acetates such as ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, and isobutyl acetate. The solvent may be used alone or in combination of two or more.

[0072] The drying of the coating liquid may be performed by adjusting the drying temperature and drying time depending on the type and amount of the solvent used. The drying of the coating liquid is preferably performed, for example, by heating the applied coating liquid at 40 to 150°C.

[0073] In the patch of the present invention, as described above, the storage stability of Blonanserin is improved by using an organic acid. Therefore, even if the patch is stored for a long period of time, precipitation of Blonanserin is reduced, and this can reduce the change in transdermal absorbability of Blonanserin before and after storage. In addition, the patch can exhibit high storage stability of Blonanserin not only when stored in a room temperature environment, but also when stored in a high temperature environment. Therefore, it is possible to easily manage the temperature during storage of the patch.

[0074] Furthermore, in the adhesive layer containing the tackifier (B1), by setting the molar ratio and mass ratio of the organic acid to blonanserin within a predetermined range, it is possible to reduce the bleeding out of the organic acid from the adhesive layer. Therefore, according to the patch of the present invention, it is also possible to reduce the overdosing of blonanserin and the decrease in adhesiveness caused by the bleeding out of the organic acid.

[0075] The use form of the patch is not particularly limited, but the patch is preferably used by directly attaching the adhesive layer to the skin. Since the patch of the present invention has sufficient adhesiveness to the skin, the above-mentioned use form can particularly exhibit the effects of the present invention. EXAMPLES

[0076] The present invention will be described in more detail below using examples, but the present invention is not limited thereto.

[0077] Details of each component used in the examples and comparative examples are described below.

[0078] (Rubber adhesive base) Styrene-isoprene-styrene block copolymer (SIS block copolymer, no acidic functional group, styrene unit content: 22% by mass, viscosity of 25% by mass toluene solution at 25°C: 1000 mPa·s, manufactured by KRATON POLYMERS, product name "KRATON (registered trademark) D1111")

[0079] (Tackifier (B1)) Tackifier (B1-1) (terpene resin, no acidic functional group in the molecule, acid value: 0 mg KOH / g, Yasuhara Chemical Co., Ltd. product name "YS Resin PX1150N") Tackifier (B1-2) (hydrogenated alicyclic petroleum resin, does not have acidic functional groups in the molecule, acid value: 0 mg KOH / g, manufactured by Arakawa Chemical Industries, Ltd., product name "Arcon P-100")

[0080] In addition, the tackifiers (B1-1) and (B1-2) do not have an acidic functional group in the molecule, and therefore do not have an acid value due to their molecular structure, and therefore the acid value of the tackifiers (B1-1) and (B1-2) is recorded as "0 mgKOH / g".

[0081] (Examples 1 to 6 and Comparative Examples 1 to 4) A mixture was obtained by mixing a rubber-based adhesive base, a tackifier (B1), and levulinic acid (melting point 33°C) with 80 parts by mass of toluene and stirring until homogenous so as to obtain an adhesive layer containing the respective contents shown in Table 1. To this mixture, free base type blonanserin and octyldodecanol were added so as to obtain an adhesive layer containing the respective contents shown in Table 1, and 42 parts by mass of toluene was further added. The mixture was stirred until homogenous so as to obtain a coating liquid for forming an adhesive layer.

[0082] A release-treated polyethylene terephthalate film was prepared as a release liner (thickness: 75 μm). A coating liquid was applied to the silicone release-treated surface of this polyethylene terephthalate film, and the coating was dried to obtain an adhesive layer (thickness: 80 μm). A polyethylene terephthalate film (thickness: 38 μm) was prepared as a support. This support was superimposed on the adhesive layer, and the adhesive layer was transferred to the support and laminated together to produce a patch.

[0083] In all of the patches of the Examples and Comparative Examples, immediately after production, free base blonanserin was dissolved in the adhesive layer without precipitating as crystals.

[0084] The content (mass%) of each component contained in the adhesive layer is shown by a numerical value not enclosed in parentheses in the column "Composition of adhesive layer" in Table 1. Furthermore, the content (parts by mass) of each component in the adhesive layer converted into the content ratio relative to 100 parts by mass of the rubber-based adhesive base is shown by a numerical value enclosed in parentheses in the column "Composition of adhesive layer" in Table 1.

[0085] [evaluation] The storage stability and bleed-out resistance of blonanserin in the patches obtained in the Examples and Comparative Examples were evaluated according to the following procedures. The results are shown in Table 1.

[0086] [Storage stability of Blonanserin: stored at 25°C] Immediately after production, the patch was punched out to prepare a flat square test piece (area: 3 cm 2 ) were obtained. Each test piece was sealed in an aluminum package and stored in an atmosphere at 25°C. After one week, one month, three months, and six months, the aluminum packages were opened in sequence and the test pieces were removed from the aluminum packages. The release liner was removed from the test pieces to expose the adhesive layer surface, which was observed under a polarizing microscope (magnification 100x) to observe whether crystals were precipitated and judged based on the following criteria.

[0087] <Judgment criteria> A: No crystals were precipitated even after half a year of storage. B: No crystals had precipitated after three months of storage, but crystals had precipitated after six months. C: No crystals had precipitated after one month of storage, but crystals had precipitated after three months. D: No crystals were precipitated after one week of storage, but crystals were precipitated after one month.

[0088] If crystals were found to precipitate after one month of storage, further storage was discontinued, and if crystals were found to precipitate after three months of storage, further storage was discontinued.

[0089] [Storage stability of Blonanserin: Storage at 40℃ or 50℃] Immediately after the production of the patch, the patch was punched out to produce a flat square test piece (area: 3 cm 2 ) was obtained. Next, the release liner was removed from the test piece to expose the surface of the adhesive layer. A very small amount of blonanserin powder (diameter: 1 to 10 μm) was scattered as seed crystals in the center of the adhesive layer surface. The scattered blonanserin powder was photographed using a polarizing microscope (magnification 100 times), and the obtained image of the blonanserin powder was recorded as the "initial state."

[0090] The test specimens were sealed in aluminum packaging and stored for 7 days in an atmosphere at 40° C. or 50° C. After storage, the test specimens were removed from the aluminum packaging, and the same blonanserin powder as above was photographed using a polarizing microscope (magnification 100 times), and the obtained images of the blonanserin powder were recorded as "state after storage."

[0091] The images of the Blonanserin powder in the initial state and after storage were compared, and the change in size of the scattered Blonanserin powder was judged based on the following criteria. <Judgment criteria> A: The diameter of the sprayed blonanserin powder decreased. B: The diameter of the sprayed blonanserin powder did not shrink or increase, and no change was observed. C: The diameter of the scattered blonanserin powder increased, but the diameter growth range of the single blonanserin powder particle with the largest increase in diameter was 25 μm or less. D: The diameter of the dispersed blonanserin powder increased, and in one blonanserin powder particle with the largest increase in diameter, the diameter growth width exceeded 25 μm.

[0092] The diameter of the Blonanserin powder means the diameter of the smallest perfect circle that can surround the Blonanserin powder. The growth range of the diameter of the Blonanserin powder is the value obtained by subtracting the diameter of the Blonanserin powder in the initial state from the diameter of the Blonanserin powder after storage.

[0093] The above-mentioned evaluation method for storage stability under an atmosphere of 40° C. or 50° C. is also generally called the Crystal Seeding method (CS method). Based on the evaluation results of the CS method, the long-term storage stability of blonanserin can be predicted as follows.

[0094] The grade "A" means that the solubility of Blonanserin in the adhesive layer of the test piece is equal to or lower than the saturated solubility, and there is a very high possibility that Blonanserin will not precipitate over time and will remain stably contained in a dissolved state. The grades "B" and "C" mean that the solubility of Blonanserin in the adhesive layer of the test piece is close to the saturated solubility, and there is a high possibility that Blonanserin will not precipitate over time and will remain stably contained in a dissolved state. The grade "D" means that the solubility of Blonanserin in the adhesive layer of the test piece is equal to or higher than the saturated solubility, and there is a possibility that Blonanserin will precipitate as crystals over time, resulting in a decrease in transdermal absorbability.

[0095] [Bleed-out resistance] Immediately after production, the patch was punched out into a flat square test piece (area: 3 cm 2 The test specimen was sealed in an aluminum package and stored at room temperature for one day. The test specimen was then removed from the aluminum package.

[0096] Next, the release liner was removed from the test piece to expose the surface of the adhesive layer. The test piece was placed on the SUS plate so that the adhesive layer was in contact with the SUS plate, and the test piece was pressed against the SUS plate by rolling it back and forth with a 2 kg hand roller. 24 hours after pressing, the test piece was peeled off at a peel angle of 180°, and the appearance of the test piece and the SUS plate were judged based on the following criteria.

[0097] <Judgment criteria> A: After peeling, no peeling was observed at the interface between the adhesive layer of the test piece and the support, and no traces (cloudiness) of the test piece were observed at the affixed location on the SUS plate. B: After peeling, no peeling was observed at the interface between the adhesive layer of the test piece and the support, and slight cloudiness was observed at the SUS plate where the test piece was attached. C: After peeling, no peeling was observed at the interface between the adhesive layer of the test piece and the support, and cloudiness was observed at the affixed area of ​​the SUS plate. D: After peeling, peeling was observed at the interface between the adhesive layer and the support of the test piece.

[0098] A grade of "D" indicates that a large amount of liquid components, believed to be organic acids, have bled out to the interface between the adhesive layer and the backing of the test specimen. A patch in this state is not suitable as a patch because it may cause a decrease in adhesion to the skin, the adhesive layer to remain on the skin when removed, or an overdose of blonanserin.

[0099] [Transdermal absorption of blonanserin] The patch was punched out to create a flat square test piece (area: 3 cm 2 Blonanserin was extracted from the adhesive layer of one of the test pieces, and the amount of extracted Blonanserin was measured by HPLC (high performance liquid chromatography) and recorded as the "amount of Blonanserin before the test."

[0100] Next, the release liner was peeled off from the remaining test piece to expose the adhesive layer entirely, and the test piece was then attached to the back of a rat whose back had been shaved for 24 hours. After peeling the test piece off from the rat's back, Blonanserin was extracted from the adhesive layer of the test piece, and the amount of Blonanserin extracted was measured using HPLC, and was recorded as the "amount of Blonanserin after the test". The value obtained by subtracting the amount of Blonanserin after the test from the amount of Blonanserin before the test was recorded as the amount of percutaneous absorption.

[0101] The transdermal absorbability of Blonanserin was evaluated for the patches of Examples 1 and 4, and for a patch (manufactured by Sumitomo Pharma under the trade name "Lonasen Tape 40 mg") as Comparative Example A. Comparing the amount of percutaneous absorption, the patch of Example 1 exhibited a percutaneous absorption amount that was "5.76 times" that of the Lonasen Tape of Comparative Example A, and the patch of Example 4 exhibited a percutaneous absorption amount that was "5.61 times" that of the Lonasen Tape of Comparative Example A, demonstrating sufficient percutaneous absorbability.

[0102] The patch of Comparative Example A was produced by the following method.

[0103] Under an inert gas atmosphere, 75 parts by mass of 2-ethylhexyl acrylate, 22 parts by mass of N-vinyl-2-pyrrolidone, 3 parts by mass of acrylic acid and 0.2 parts by mass of azobisisobutyronitrile were solution polymerized in ethyl acetate at 60° C. to obtain an acrylic polymer.

[0104] 55.94 parts by mass of an acrylic polymer, 6.46 parts by mass of free base type blonanserin, 17.77 parts by mass of isopropyl myristate, 14.54 parts by mass of sesame oil, 0.97 parts by mass of 2,6-di-tert-butyl-4-methylphenol (BHT), 1.26 parts by mass of magnesium aluminometasilicate (Neusilin (trade name) type: UFL2, manufactured by Fuji Chemical Industry Co., Ltd.), were mixed thoroughly with an appropriate amount of ethyl acetate until homogeneous, and then 0.06 parts by mass of a trifunctional isocyanate was added as a crosslinking agent. (Coronate HL (manufactured by Nippon Polyurethane Industry Co., Ltd.) was added, the solids concentration was adjusted to 24 mass% with ethyl acetate, and the mixture was thoroughly stirred until homogenous, obtaining an adhesive layer solution. A 75 μm thick polyethylene terephthalate film that had been subjected to silicone release treatment was prepared as a release liner, and the obtained adhesive layer solution was applied to the silicone release treated surface of the release liner and dried to form an adhesive layer. The adhesive surface of the formed adhesive layer was then bonded to a 3.5 μm thick polyethylene terephthalate film and a 12 g / m2 coating. 2 A laminate was prepared by laminating the polyethylene terephthalate nonwoven fabric and the nonwoven fabric side of the support laminated thereto. Then, the laminate was left at 70°C for 48 hours, and the acrylic polymer in the adhesive layer was crosslinked with a crosslinking agent. After leaving the laminate, the release liner was peeled off, and the adhesive layer was allowed to contain lactic acid so that the final content of lactic acid was 3 parts by mass per 97 parts by mass of the adhesive layer. Then, a release liner identical to the release liner was prepared separately, and the silicone release-treated surface of the release liner was laminated to the adhesive layer so that the adhesive layer faced each other, to produce a patch. The thickness of the adhesive layer was 80 μm.

[0105] [Table 1] [Industrial Applicability]

[0106] According to the present invention, even though the adhesive layer contains an organic acid, the bleed-out of the organic acid is reduced, and a patch having excellent storage stability of blonanserin can be provided.

Claims

1. A support and an adhesive layer laminated and integrated on one surface of the support, The adhesive layer is Blonanserin, A rubber-based adhesive base; Organic acids, A tackifier (B1) having an acid value of less than 2 mgKOH / g; A patch, wherein in the adhesive layer, a molar ratio of the organic acid to the blonanserin is 0.30 or more, and a mass ratio of the organic acid to the blonanserin is less than 0.

45.

2. 2. The patch according to claim 1, wherein the rubber-based adhesive base contains at least one of a styrene-based polymer and polyisobutylene.

3. 2. The patch according to claim 1, wherein the rubber-based adhesive base contains a styrene-isoprene-styrene block copolymer.

4. The patch according to any one of claims 1 to 3, characterized in that the organic acid comprises levulinic acid.

5. 2. The patch according to claim 1, wherein the mass ratio of the tackifier (B1) to the organic acid in the adhesive layer is 12 or more and 50 or less.

Citation Information

Patent Citations

  • Novel tape preparation

    WO2007142295A1

  • Blonanserin-containing patch and production method therefor

    WO2021230064A1